EFEKTIVITAS RESTRUKTURISASI PEMBIAYAAN, FDR DAN NPF TERHADAP PROFITABILITAS PERUSAHAN SELAMA MASA PANDEMI COVID-19 (STUDI PADA BANK SYARIAH DI INDONESIA) - Meilinda, Bunga Putri; Muttaqin, Aminullah Achmad (Islamic Economics Program, Faculty of Islamic Economics and Business, 2021)
This study aims to determine the effect of the financing restructuration, financing to deposit ratio, and non performing financing on company’s profitability represented by return on assets during the covid-19 pandemic.the analytical method used is quantitative research with panel data regression alaysis techniques. The result of this study indicate that financing restructuration has a positive significant effect on the company’s profitability during the covid-19 pandemic of 0,430932 and financing to deposit ratio has a negative effect on the company’s profitability during the covid-19 pandemis of -0,428821. Meanwhile, non performing financing doesn’t have a significant effect on the company’s profitability during the covid-19 pandemic.